Association between anxiety and frailty in postmenopausal women - Alicia García-Vigara; Julio Fernandez-Garrido; Peter Chedraui; Aitana Monllor-Tormos; Miguel Ángel García-Pérez; Juan José Tarín; Arturo Artero; Antonio Cano (Taylor & Francis Group, 2024)
AbstractObjective To explore the association between anxiety and frailty in community-dwelling postmenopausal women.Methods This was a cross-sectional study in which 390 postmenopausal women (aged 60-83 years) who were attending a comprehensive care program were surveyed between January 2018 and February 2020. Each participant was administered a validated Spanish version of the Hospital Anxiety and Depression Scale (HADS) to assess their anxiety status. Those scoring 8 or higher on the anxiety subscale of the HADS were indicative of anxiety. The assessment of frailty utilized the Fried's phenotype, with a diagnosis of frailty established if the participant met at least three out of the five criteria. Factors associated with frailty were analyzed using multivariate logistic regression.Results The mean age of participants was 70.08 years, with an average of 12.58 ± 3.19 years since menopause. Frailty was diagnosed in 43.85% of the total series, while anxiety was present in 41.08%, rising to 69.59% in participants with frailty. Neither body mass index, years since menopause, educational level, economic status, nor smoking habit demonstrated significant associations with frailty. Upon multivariate analysis, anxiety (OR 8.56), multimorbidity (OR 2.18), and age (OR 2.73) emerged as independently associated with frailty (p < .001, p = .005, and p < .001, respectively).Conclusions Among postmenopausal women with frailty, anxiety was detected in over two thirds of cases and was independently associated with frailty. This underscores the relevance of implementing anxiety screening in comprehensive care programs for postmenopausal women, with the goal of improving frailty through anxiety diagnosis and treatment.